Learning to Read in Times of COVID-19 Theoretical Review - et al., Blanca Esther Lazaro-Aguilar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this theoretical review research is to analyze and reflect on the process of learning to read in elementary school students in a context of confinement by COVID-19. To this end, 20 articles were reviewed from the Scopus, Scielo and EBSCO databases, in Open Access, in the range 2020-2921; the search equations were: "oral communication" AND COVID-19, "elementary school students" AND COVID-19. The research analyzed shows how each nation in the world has assumed the challenges of giving continuity to the education provided at all levels, in this case it has been analyzed at the primary level, in which the efforts and performances of all the actors of education have been observed to continue in this process of educating under the context of COVID-19. Thus, it has been seen how teachers have generated new strategies to direct teaching and learning in order to give continuity of training and education to their students, assuming the challenges of adaptation and adaptation to this new context with the mandatory use of technology and virtuality. The analysis has focused on the learning of reading in times of COVID-19, where it has been found in the research analyzed that the context significantly influences the learning of reading, therefore it is necessary the implementation of strategies by teachers that generate and motivate students to perform activities that lead them to read and understand, since it is evident that having a good reading quality leads students to understand and reflect on the context that surrounds them, allowing them to make decisions that improve their quality of life.